Genome-wide association study of warfarin maintenance dose in a Brazilian sample. (July 2015) - Parra, Esteban J; Botton, Mariana R; Perini, Jamila A; Krithika, S; Bourgeois, Stephane; Johnson, Todd A; Tsunoda, Tatsuhiko; Pirmohamed, Munir; Wadelius, Mia; Limdi, Nita A; Cavallari, Larisa H; Burmester, James K; et al.
Aim: Extreme discordant phenotype and genome-wide association (GWA) approaches were combined to explore the role of genetic variants on warfarin dose requirement in Brazilians.Methods: Patients receiving low (≤20 mg/week; n = 180) or high stable warfarin doses (≥42.5 mg/week; n = 187) were genotyped with Affymetrix Axiom ® Biobank arrays. Imputation was carried out using data from the combined 1000 Genomes project.Results : Genome-wide signals (p ≤ 5 × 10 -8 ) were identified in the well-known VKORC1 (lead SNP, rs749671; OR: 20.4; p = 1.08 × 10 -33 ) and CYP2C9 (lead SNP, rs9332238, OR: 6.8 and p = 4.4 × 10 -13 ) regions. The rs9332238 polymorphism is in virtually perfect LD with CYP2C9*2 (rs1799853) and CYP2C9*3 (rs1057910). No other genome-wide significant regions were identified in the study.Conclusion : We confirmed the important role of VKORC1 and CYP2C9 polymorphisms in warfarin dose. Original submitted 14 January 2015; Revision submitted 26 May 2015